Promoting mobile collaborative language learning in Islamic higher education - Rully Agung Yudhiantara; Ade Yeti Nuryantini (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2019)
This study sought to explore students’ experience in using Instagram to participate in mobile collaborative language learning (MCLL). The contents they produced and shared, as well as their interaction and collaboration, were analyzed. The participants of this study were 110 students in an English education department, in three different classes,who all had taken a translation coursetheir third semester. Online tasks were assigned to students and they were required to produce, share, interact and collaborate to accomplish tasks. This study applied a qualitative method with case study research design using observation, focus group discussion and content analysis. Data were analyzed through stages namely categorization, reduction and interpretation. Results showed that the students were able to participate in MCLL using Instagram. They produced and shared contents that met the requirement of MCLL. The contents included English sentences for structural collaboration in terms of subject-verb agreement and English sentences for word meaning collaborations. They interacted with their peers by writing feedback and comments on the uploaded content. They collaborated with their peers by providing multiple interactions to accomplish tasks in MCLL like writing structural analysis, word meaning, paraphrasing sentences, and sentence translation.